A critical investigation on viscosity and tribological properties of molybdenum disulfide nano particles on diesel oil. (2021) - Ramesh, P.; Sai Krishnan, G.; Pravin Kumar, J.; Bakkiyaraj, M.; Pradhan, Raghuram; Ganesh babu, L.
Abstract: Tribological properties are one of the important parameters of examining the performance of the diesel oil. Diesel oil is predominantly used everywhere and it is one of the important essentials in daily living. This study aims to examine the tribological and the thermo physical properties of molybdenum disulfide nano particles. In this work the nano particles were dispersed in 3 different concentrations such as 0.3, 0.5 and 0.7 weight percentages with the pure diesel oil. Molybdenum disulfide nano particles were immersed in diesel oil at different proportions. In this work a pin on disc tribometer were utilised to analyze the frictional properties. Wear properties of Molybdenum disulfide (MoS2 ) nano particles were analysed. The results reveal that the addition of molybdenum nano particles marginally reduced the wear properties. The other key properties such as nano fluids viscosity, viscosity index obtained the highest values at 0.7 weight percentages. Based on the results it was concluded that the frictional property had no impact on the anti friction and anti wear properties at different concentrations with diesel oil.